Evaluation of Metalloproteinase-8 Levels in Crevicular Fluid of Patients with Healthy Implants or Periodontitis - Paweł Aleksandrowicz; Paulina Żelechowska; Justyna Agier; Katarzyna Starska; Krzysztof Kędzierski; Joanna Wysokińska-Miszczuk; Ewa Brzezińska-Błaszczyk (Hindawi Limited, 2017)
Evaluation of periodontal and peri-implant tissue condition is mainly based on clinical examination and imaging diagnostics. Some data imply that Metalloproteinase-8 (MMP-8) level examination in peri-implant sulcular fluid (PISF) might be useful for evaluating the condition of peri-implant tissues and monitoring a development of peri-implant inflammation, including both mucositis and peri-implantitis. Hence, in this study, we decided to evaluate the level of MMP-8 in PISF obtained from patients without clinical symptoms of mucositis or peri-implantitis and compare it with MMP-8 level in gingival crevicular fluid (GCF) obtained from patients with healthy periodontium and those with varying severity of periodontitis. A total of 189 subjects were included in the study, and GCF/PISF samples were analysed for MMP-8 level by ELISA test. We documented that MMP-8 level in PISF obtained from patients without symptoms of mucositis or peri-implantitis was significantly higher not only than in GCF of periodontally healthy patients but also, which seems to be very interesting, than in GCF of patients with varying degrees of periodontal inflammation, consistent with earlier studies. Our observation might imply that monitoring of MMP-8 level in PISF could help to diagnose mucositis/peri-implantitis in an early stage, prior to clinical manifestations, which may allow for quick start of appropriate therapy.